Persepsi mahasiswa PGSD terhadap rencana implementasi guru bimbingan dan konseling di sekolah dasar - Eko Perianto (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
This is a descriptive research and does not mean to test hypothesis but to describe phenomenon as it is by using numbers as symptom observed. The purpose of this study is to determine the perception of students on the implementation plan of teacher’s guidance and counseling in elementary school. Furthermore, in this research which is used as subject of this research is student of elementary school teacher education which is taking Guidance and Counseling in elementary school in for Academic Year 2016/ 2017. The data analysis technique used is Descriptive statistics with percentage techniques. The results showed that students' perceptions of the implementation of teacher guidance and counseling in elementary school based on the overall calculation then obtained the value of the general perception of students that is 72.81% . This means that students have a perception of the implementation plan of guidance and counseling in elementary school in good category.